Probing the chemical stability between current collectors and argyrodite Li6PS5Cl sulfide electrolyte - Artur Tron; Alexander Beutl; Irshad Mohammad; Andrea Paolella (Communications Chemistry)
Abstract Recently, sulfide-based electrolytes, including the argyrodite family (Li6PS5X, X = Cl, Br, I), are considered promising candidates for all-solid-state battery fabrication due to their high ionic conductivity. However, from the industrial point of view, other parameters such as the chemical and electrochemical stability toward current collectors are equally important, but often neglected. Although many efforts have been directed toward the investigation, optimization and testing of sulfide electrolytes into a press device (10 MPa) with a stainless-steel current collector, the investigation of the current collector’s behavior in contact with sulfide solid electrolytes in coin cell (0.2 MPa) or pouch cell (0.1-0.2 MPa) formats is still an open question. In this work, the systematic physicochemical and electrochemical analyses of copper, nickel, stainless steel, aluminum, and aluminum-carbon current collectors in contact with the Li6PS5Cl electrolyte in coin cell format configuration is reported, enabling the understanding of the reaction mechanisms. While SS, Ni, Al and Al/C show good chemical stability, Cu, Li, and Cu/Li have high corrosion susceptibility in sulfide electrolytes. Therefore, this study supports the selection of appropriate current collectors for fabricating sulfide-based components, especially via the wet chemistry process which is a promising approach for the industrialization of solid-state batteries with sulfide electrolyte.